The Needs and Readiness of the Islamic Banks to Adopt the Comprehensive Islamic Accounting Standards: The Malaysian Experience - Abdul Fatah, Muhammad Mukhlis; Md. Thani, Azlan bin; Muhammad, Anuar bin; Mohamad Azhan, Maisarah binti; Mohamad, Nujba binti; Ismail, Nur Iylia Amni binti (Information Management and Business Review, 2024)
The Islamic finance sector in Malaysia has seen substantial growth over the past few decades, becoming one of the leading markets for Islamic financial products and services. This growth has brought about significant challenges in financial reporting, primarily due to the limitations of conventional International Financial Reporting Standards (IFRS) in addressing the unique characteristics of Islamic financial transactions. The shari’ah transactions are governed by Shariah principles, which prohibit interest (riba) and emphasize on risk-sharing, ethical investments, and social justice. The study aims to provide a comprehensive analysis of the current issues and debates surrounding the need for comprehensive Islamic accounting standards in Malaysia. It will review recent literature, regulatory developments, and the experiences of practitioners in the particular field. Furthermore, the report seeks to highlight the readiness of Bank Negara Malaysia and all Islamic Banks to adopt Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) standards and explore the feasibility of integrating these standards within the International Financial Reporting Standard (IFRS) framework. Additionally, this report aims to contribute to the ongoing discourse on Islamic accounting by offering critical insights and recommendations for policymakers, regulators, and financial institutions. The ultimate goal is to enhance the transparency, comparability, and reliability of financial reporting in the Islamic finance sector, thereby promoting its sustainable growth and integration into the global financial system.